World University Rankings - Basu, Aparna (Journal of Information and Knowledge, 2013)
Performance Evaluation of Academic and Research Institutions is important from the point of several groups such as funding agencies, students, employers, etc. For some years now, rankings have been produced by different agencies around the world. Scientometric methods using research publication and citation data feature in almost all rankings of research excellence. In this article we try to summarize the criteria used by some of these agencies. In particular we note the presence of only a few Indian institutes in these rankings. The need for initiating a systematic ranking of Indian institutes at regular intervals is stressed.